2002
DOI: 10.1038/nature01146
|View full text |Cite
|
Sign up to set email alerts
|

Self-recognition promotes the foreign antigen sensitivity of naive T lymphocytes

Abstract: A 72 kb region of BAC259.12D that encompasses the HAR1 locus was sequenced in its entirety using a DNA Sequencing Kit (PE Applied Biosystems) with an automated DNA sequencer (ABI PRISM 3100; PE Applied Biosystems). HAR1 complementary DNA was cloned from a cDNA library of L. japonicus shoots using DNA fragments of the first exon of the HAR1 gene obtained by polymerase chain reaction (PCR) from BAC259-12D. After sequencing the cDNA clone, the full-length cDNA sequence was determined by 5 0 rapid amplification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
347
3
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(374 citation statements)
references
References 30 publications
22
347
3
2
Order By: Relevance
“…4 It has been shown that PB T cells are de-sensitized and need to be re-sensitized after entering lymph nodes or tissue [19]. Therefore, it would be interesting to compare sensitized T lymphocytes with LP T cells from inflamed intestinal tissue.…”
Section: Analysis Of Calcium Signals In T Lymphocytes Of Inflamed Andmentioning
confidence: 99%
“…4 It has been shown that PB T cells are de-sensitized and need to be re-sensitized after entering lymph nodes or tissue [19]. Therefore, it would be interesting to compare sensitized T lymphocytes with LP T cells from inflamed intestinal tissue.…”
Section: Analysis Of Calcium Signals In T Lymphocytes Of Inflamed Andmentioning
confidence: 99%
“…Support data for this second hypothesis came from recent reports showing that dendritic cells signal to T cells in the absence of exogenous antigens and that self-recognition maintains CD4 ϩ T-cell clones in optimal state of antigen sensitivity. 37,38 To decide between the 2 hypotheses described above, we used the TCR transgenic mice DO11.10. 28 All the T cells present in these mice are CD4 ϩ and carry a TCR specific for OVAp ϩ I-A d , an antigen that is not present in BM microenvironment.…”
Section: Antigen-primed T Cells Maintain Normal Hematopoiesismentioning
confidence: 99%
“…The main difficulty is that the self-nonself theory grounds the question of the boundaries of a living thing in a question of origin: everything that comes from the outside triggers a rejection response, while everything that comes from the inside does not trigger an immune response. Yet self constituents can trigger immune responses in healthy conditions (Anderton and Wraith 2002;Wing and Sakaguchi 2010;Germain 2012;Wynn et al 2013) (Sakaguchi 2000;Bouneaud et al 2000;Stefanová et al 2002;Savill et al 2002;Taylor et al 2004;Sakaguchi 2006;Zehn and Bevan 2006;Germain 2012; Okabe and Medzhitov 2016) (this aspect was anticipated by Jerne (1974), and has been discussed by Tauber (1994) and Cohen (2000)). Moreover, many nonself constituents, including many microbes (as shown by recent work on symbiosis), are not rejected by the immune system (Hooper and Gordon 2001;Chu and Mazmanian 2013).…”
Section: Delineating the Physiological Individual: An Immunological Pmentioning
confidence: 97%